Sentido e alcance do princípio da função social da propriedade urbana: a ausência de plano diretor e o conteúdo mínimo dedutível do sistema da constituição federal brasileira de 1988 - Erenberg, Jean Jacques (2007)
The present paper work aims at showing that the urban property social function principle has a minimum content, legal and mandatory, that can be extracted of the Brazilian constitutional system since the promulgation of the Federal Constitution in October, 5, 1988 and that does not depend on City Plannig Law presence to happen in a full form, direct and immediate on all urban property in the domestic territory. To support that affirmation, first we chose the study of the principles, searching to find its importance and to identify the points of contact and distance of these in relation to the juridical rules; after that we tried to locate the role of the managing plan, pointing the hypotheses of obligatoriness in constitutional and infraconstitutional levels and the consequences of not editing that plan, when it is obligatory; then we made some relevants questionings about the new constitutional profile of the property by the positioning of the social function as an intrinsic and forming element of its concept, capable to assure its effectiveness in a State of social welfare. Finally we had proceeded an analysis of the property social function in general and then of the urban property in special. The study concludes that, in fact, it is possible to extract of the Brazilian constitutional system after-1988 an essential legal content to the social function of the urban property principle, capable to make valid the underlying idea of fulfilment of the city social functions and fulfilment of the human life dignity basic principle. In this context, the managing plan it figures as an instrument to ensure the power of the urban property social function and not as a conditional circumstance of its existence and applicability